2013
DOI: 10.4300/jgme-d-11-00324.1
|View full text |Cite
|
Sign up to set email alerts
|

Essential Facets of Competence That Enable Trust in Graduates: A Delphi Study Among Physician Educators in the Netherlands

Abstract: Background There is a need for valid methods to assess the readiness for clinical practice of recently graduated physicians. To develop these methods, it is relevant to know the general features of trainees' performance that facilitate supervisors' trust in their ability to perform critical clinical tasks. Objective To discover such essential facets of competence (FOCs), based on the opinion of experienced physician educators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
58
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 30 publications
0
58
0
Order By: Relevance
“…Furthermore, the Dutch students ordered significantly less laboratory and radiology tests compared to the German students with no difference in the diagnostic accuracy for the five simulated patients [15]. We repeated the previous ranking study performed among physician educators in the Netherlands and Germany with 25 essential competences that enable trust in graduates [13,16]. In our study including 202 physicians from three German medical schools with different undergraduate curricula, we found 90% congruency with respect to the top 10 competences with the Dutch cohort [17].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the Dutch students ordered significantly less laboratory and radiology tests compared to the German students with no difference in the diagnostic accuracy for the five simulated patients [15]. We repeated the previous ranking study performed among physician educators in the Netherlands and Germany with 25 essential competences that enable trust in graduates [13,16]. In our study including 202 physicians from three German medical schools with different undergraduate curricula, we found 90% congruency with respect to the top 10 competences with the Dutch cohort [17].…”
Section: Introductionmentioning
confidence: 99%
“…RIME ''LEVELS'' Reporter Interpreter Interpreter Manager Educator Educator ''independent'' function, and still does not compromise patient care? Studies are underway, but this will remain a field for further research for quite some time in which trust seems a key element (Kennedy et al 2005;Sterkenburg et al 2010;Wijnen-Meijer et al 2013). Newer frameworks and approaches, like RIME, may have a higher burden of proof than more traditionally accepted approaches like ''KSA.''…”
Section: The Hybrid Nature Of Most Frameworkmentioning
confidence: 99%
“…In addition to this editorial, they include a perspective on the entrustment process, 11 an exploration of the attributes of competence that enable entrustment decisions, 12 and a succinct description in one of this issue's Rip Outs. 13 Hauer et al 14 and Shaughnessy et al 15 applied the EPA concept to internal medicine and family medicine and identified 30 and 76 EPAs, respectively.…”
mentioning
confidence: 99%
“…9,16 The RANZCP has included both general activity-focused EPAs and specific medical condition EPAs in psychiatry training, in a staged curriculum description: general activities, such as ''producing discharge summaries and organizing appropriate transfer of care,'' ''communicating with a family about a young adult's major mental illness,'' ''violence risk assessment and management in forensic psychiatry,'' and ''interviewing Mā ori,'' and medical conditions, such as ''care for a patient with delirium,'' ''initiating an antipsychotic medication in a patient with schizophrenia,'' and ' ' 12 show how discernment of one's own limitations, taking responsibility, and dealing with mistakes are among the qualities educators take into account when making entrustment decisions. Again, different authors have sought to indentify these qualities with different wording, 17,18 but much of the underlying concepts seem similar.…”
mentioning
confidence: 99%